2015
DOI: 10.3390/ijms16011907
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Stimulates Dendrite Formation and Complexity in the Hilar Zone of the Rat Hippocampus: Participation of the Ca++/Calmodulin Complex

Abstract: Melatonin (MEL), the main product synthesized by the pineal gland, stimulates early and late stages of neurodevelopment in the adult brain. MEL increases dendrite length, thickness and complexity in the hilar and mossy neurons of hippocampus. Dendrite formation involves activation of Ca2+/Calmodulin (CaM)-dependent kinase II (CaMKII) by CaM. Previous work showed that MEL increased the synthesis and translocation of CaM, suggesting that MEL activates CaM-dependent enzymes by this pathway. In this work we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 75 publications
1
32
0
Order By: Relevance
“…In addition to its chronobiotic effect, melatonin participates in the modulation of neuronal functions, neurodevelopment at early and late stages (Kong et al , ; Chen et al , ) and affects brain structures underlying sleep regulation (Ochoa‐Sanchez et al, ), drug‐related learning (Wang et al, ; Savaskan et al, ) and reward (Hutchinson et al, ; Clough et al, ). MT receptors mediate the melatonin‐induced increase in dendrite length, thickness and complexity of hippocampal neurons, as these effects were partially blocked by luzindole (Dominguez‐Alonso et al, ). Similarly, melatonin‐induced differentiation and maturation of adult neural stem cells were almost abolished in the presence of luzindole (de la Fuente Revenga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its chronobiotic effect, melatonin participates in the modulation of neuronal functions, neurodevelopment at early and late stages (Kong et al , ; Chen et al , ) and affects brain structures underlying sleep regulation (Ochoa‐Sanchez et al, ), drug‐related learning (Wang et al, ; Savaskan et al, ) and reward (Hutchinson et al, ; Clough et al, ). MT receptors mediate the melatonin‐induced increase in dendrite length, thickness and complexity of hippocampal neurons, as these effects were partially blocked by luzindole (Dominguez‐Alonso et al, ). Similarly, melatonin‐induced differentiation and maturation of adult neural stem cells were almost abolished in the presence of luzindole (de la Fuente Revenga et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, melatonin also enhances neurite enlargement by antagonizing the Ca 2+ ‐calmodulin (CaM)‐dependent microtubule depolymerization . Recently, it was demonstrated that melatonin induces the dendritogenesis process in the hilar zone of the hippocampus through CaM translocation to the soluble fraction and CaM‐kinase II stimulation, indicating that it plays a key role in neuronal development and differentiation in the adult brain . Also, in cultured embryonic hippocampal neurons, melatonin stimulates axonal formation through MT2 receptors and activation of MT1 receptor has been implicated in neurite formation at earlier stages …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that melatonin influenced cAMP formation [ 27 ], protein kinase A activity and phosphorylation of the cAMP-responsive element binding protein (CREB) [ 26 ]. Melatonin also can stimulate c-Jun N -terminal kinase activity, influence the generation of intracellular Ca 2+ [ 28 ] and promote PKC activity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%